Pola Saluran Pemasaran Beras di Kecamatan Tanjung Lago, Kabupaten Banyuasin - Yos Karimudin (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
The purpose of this study is to first look at the pattern of rice marketing channels and to find out the factors that influence it in Tanjung Lago District, Banyuasin Regency. This research was conducted in Tanjung Lago district, Banyuasin Regency in September - November 2019. The selection of the location of this study was carried out deliberately with the consideration that the majority of residents in Tanjung Lago district Banyuasin Regency are rice farmers, there is a village market, and is an area of rice production centres. The method used in this study is a quantitative descriptive method with surveys and interviews in which the sampling is used a simple random sampling method by taking 100 respondents. The results of this study indicate that rice marketing institutions have formed a marketing pattern consisting of four marketing channels. Factors that have a significant effect on the pattern of rice marketing channels are farm-level selling prices, marketing margins, and marketing efficiency. Marketing channel 1 is the shortest marketing channel, which has produced the smallest marketing margin value of 23.65%. The selling price of farmers' grain/rice, marketing margins, and marketing efficiency partially or simultaneously significantly influences the average farmer share of 67.69%.